IoT, RFID, and Lean Tools: An Innovative Strategy to Improve OTIF in the Logistics Chain of a Clothing Marketing Company - Manuel-Cierto, Nelba; Villayzan-Palomino, Jordan; Saenz-Moron, Martin; Straujuma, Anita (LACCEI, 2025)
In the Peruvian fashion retail sector, companies operating with manual processes face significant logistical challenges that affect their OTIF compliance. This study was conducted in a mid-sized company dedicated to the marketing of well-known brand apparel, which has an OTIF level of 81.61%, below the desired standard. Through a detailed diagnosis, three critical causes were identified: errors in manual label placement, incorrect SKU selection, and packaging inspection failures, with impacts of 41.5%, 31.1%, and 15.1%, respectively, on OTIF noncompliance. As a solution, an innovative business model was implemented, based on tool innovation structured in three components: technological innovation and Standardized Work (SW) in the labeling process, RFID, and IoT; Standardized Work (SW) in the picking process; and visual control in the final inspection through Poka-Yoke. The model was validated through a pilot test, achieving an increase in OTIF from 81.61% to 89.44%, reducing operational errors in labeling from 20.72% to 17.16%, order picking from 15.60% to 13.32%, and errors in the inspection of finished packages from 16.90% to 13.56%. In addition, average labeling time and standard picking time were reduced by approximately 58.60 to 47.20 minutes and from 78.72 to 58.21 minutes, respectively. The proposal proved to be technically and economically viable, with favorable financial indicators (NPV, IRR, and WACC). This study demonstrates how business model innovation, combined with accessible technologies, enables mid-sized companies with manual processes to advance toward digital transformation in a profitable and sustainable manner.